If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2p + -2 = 7p + 27 + -2p Reorder the terms: 5 + -2 + 2p = 7p + 27 + -2p Combine like terms: 5 + -2 = 3 3 + 2p = 7p + 27 + -2p Reorder the terms: 3 + 2p = 27 + 7p + -2p Combine like terms: 7p + -2p = 5p 3 + 2p = 27 + 5p Solving 3 + 2p = 27 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 3 + 2p + -5p = 27 + 5p + -5p Combine like terms: 2p + -5p = -3p 3 + -3p = 27 + 5p + -5p Combine like terms: 5p + -5p = 0 3 + -3p = 27 + 0 3 + -3p = 27 Add '-3' to each side of the equation. 3 + -3 + -3p = 27 + -3 Combine like terms: 3 + -3 = 0 0 + -3p = 27 + -3 -3p = 27 + -3 Combine like terms: 27 + -3 = 24 -3p = 24 Divide each side by '-3'. p = -8 Simplifying p = -8
| 50m+20m+5m=-100 | | 4y+3=x-4 | | 4+3x=-4(x-8) | | 15p+13q+p-8q-7p= | | 39=3(c+6) | | 1000x=40000 | | X+10-8+2=10 | | 4x+4(x+3)=36 | | 12x+9y=360 | | -20=5+7(y+9) | | 4.5x-40.5=13.5 | | 2a+5a-13=50 | | -2v+8=8+3v | | 27y-3y+6y=30 | | 6y-2=3 | | (6x+3)(x+5)=(2+x)(6+2x)-4 | | 3+6p=63 | | -6+5s=-71 | | -7+3y=-22 | | -6x-21=-141 | | 3X^2/20 | | 27=6d+9 | | 8x+5y+3x-2y= | | 7+4s=15 | | 900/45= | | 6+0k=256 | | 9(k-93)=18 | | 6a-6=2a+10 | | (2/3)*36 | | 2k-15=3 | | -8(-5p+4)-6=-8p+10 | | 15u-9u=30 |